2016
DOI: 10.15376/biores.11.4.8425-8434
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo-Derived Fuel from Dendrocalamus latiflorus, Phyllostachys makinoi, and Phyllostachys pubescens Waste

Abstract: Bamboo is used as a raw material for producing chopsticks, artifacts, utensils, plywood, fiberboard, and decorated multi-layered panels. The manufacturing process generates a large amount of bamboo residual waste. In this study, bamboo-derived fuels were prepared from the residual waste of Dendrocalamus latiflorus, Phyllostachys makinoi, and Phyllostachys pubescens. The combustion behaviors of bamboo-derived fuels were also investigated. The characteristics of derived fuels made from bamboo waste with engine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The authors reported values of 20.2% humidity. Lin et al [33] found values between 6.98 and 7.9% of TU for dry bamboo residues of the genus Phyllostachys.…”
Section: Basic Density Moisture Content and Proximate Chemical Analysismentioning
confidence: 99%
“…The authors reported values of 20.2% humidity. Lin et al [33] found values between 6.98 and 7.9% of TU for dry bamboo residues of the genus Phyllostachys.…”
Section: Basic Density Moisture Content and Proximate Chemical Analysismentioning
confidence: 99%
“…D. latiflorus Munro with a high economic value can produce nutrient-rich bamboo shoots, which has great benefits to humans with increasing demand. Its bamboo products are conventionally used as the raw materials for the production of chopsticks, handicrafts, utensils, plywood, fiberboard, decorative multilayer boards, and building materials [25]. We expected that various mulch materials would have varied impacts on the chemical properties of soil, leaf biochemical traits, and growth responses of D. latiflorus Munro.…”
Section: Introductionmentioning
confidence: 99%